Cytomegalovirus-associated biliary atresia - Kazuki Kodo; Kenichi Sakamoto; Tomohiko Imai; Takeshi Ota; Mitsuru Miyachi; Jun Mori; Tomohiro Chiyonobu; Tetsuya Imura; Hajime Hosoi (Elsevier, 2018)
The pathogenesis of biliary atresia (BA) is propounded to be an immunological process, but the detailed mechanisms remain unclear. In recent studies with abnormal immunological findings, T cells have drawn attention in the mechanism of BA pathogenesis. Furthermore, cytomegalovirus (CMV) infection in BA patients resulted in elevated levels of helper T cells (Th1 and Th17) and reduction of regulatory T cells. Thus, CMV infection is considered as a cause of BA.We present the case of a 3-month-old boy who presented with intracerebral hemorrhage and finally died of liver failure. BA was diagnosed on autopsy and serum CMV-IgM was positive, but CMV antigen in the liver tissue was negative.Because CMV-associated BA has poor prognosis, compared with BA not associated with CMV, accurate classification of the type of BA is essential. Keywords: Biliary atresia, Cytomegalovirus, Cytomegalovirus-associated biliary atresia